A cross-layer approach in sensing and resource allocation for multimedia transmission over cognitive UWB networks - Mohd Aripin N.; Rashid R.A.; Fisal N.; Lo A.C.C.; Ariffin S.H.S.; Yusof S.K.S. (2023)
We propose an MAC centric cross-layer approach to address the problem of multimedia transmission over cognitive Ultra Wideband (C-UWB) networks. Several fundamental design issues, which are related to application (APP), medium access control (MAC), and physical (PHY) layer, are discussed. Although substantial research has been carried out in the PHY layer perspective of cognitive radio system, this paper attempts to extend the existing research paradigm to MAC and APP layers, which can be considered as premature at this time. This paper proposed a cross-layer design that is aware of (a) UWB wireless channel conditions, (b) time slot allocations at the MAC layer, and (c) MPEG-4 video at the APP layer. Two cooperative sensing mechanisms, namely, AND and OR, are analyzed in terms of probability of detection (Pd), probability of false alarm (P f), and the required sensing period. Then, the impact of sensing scheduling to the MPEG-4 video transmission over wireless cognitive UWB networks is observed. In addition, we also proposed the packet reception rate- (PRR-) based resource allocation scheme that is aware of the channel condition, target PRR, and queue status. Copyright 2010 Norazizah Mohd Aripin et al.